(untitled) (European Journal of Interdisciplinary Research and Development, 2023)
In the study, an attempt was made to study the features of the musical and creative environment in the professional activities of a teacher. Goals and objectives of this work: consider the historical and theoretical aspects and prerequisites of the musical and creative environment (periods of formation of musical education); identify the key methodological systems of musical education and upbringing (components) as prior experience in music pedagogy; identify the features of the project method in the musical and creative environment, as a productive training for the future professional activity of a teacher.